LO21: Mentorship in Canadian emergency medicine residency training programs: a needs assessment. (15th May 2017) - Sutherland, K.A.; Pham, C.; La Riviere, C.; Weldon, E.
Abstract : Introduction: Research supports the role of mentors in the personal development and career advancement of medical trainees. Compared to non-mentored peers, mentored residents are nearly twice as likely to describe excellent career preparation and demonstrate objective career success. In prior research, only 65% of training programs in Canada had a mentorship program, and 40% indicated a need for more formal mentorship models.Methods: A needs assessment survey was distributed to RCPSC Emergency Medicine (EM) Program Directors across Canada regarding mentorship available to resident physicians training at their centers. Additionally, all EM resident and staff physicians involved in mentorship were surveyed on their perceptions of current models at their institutions. Both surveys were comprised of binary, open ended, and 5 point likert scale questions. Responses were analyzed using Fisher's exact test.Results: Eleven Program Directors responded to the survey. Formal mentorship programs were found in 82% of training centers, with 77% of programs instituted within the past 5 years. Half of resident/mentor pairings were based on a combination of identified career goals, participant personality traits, or resident request. Other pairing methods included perceived resident needs or attending physician request. Most meetings are face-to-face, with one program requiring mutual scheduled shifts. Residents identified that mentorship was significantly associated with benefits to career (p=0.0016) and niche (p=0.0019) development. Formal mentorship was felt to have a significant association with resident academic development (p=0.05) and lower rates of burnout (p=0.0018) by staff physicians. Staff mentors also associated a personal development benefit related to involvement in a mentorship relationship (p=0.0355).Conclusion: The majority of EM programs have adopted formal mentorship programs within the past 5 years. Residents and staff identify that mentorship relationships are associated with improved career and niche development as well as academic advancement. Future research will include a before and after study of the implementation of a formal mentorship program within the RCPSC-EM program at the University of Manitoba.